Evaluation of zakat literature: A bibliometric analysis and systematic literature review - Risna Putri Apriliyah; Bayu Arifianto (Center for Islamic Economics and Development Studies [P3EI], 2022)
Purpose – this study aims to determine previous research trends on zakat, assess the relationship of research collaboration, and identify future research directions.Methodology – It uses 87 articles published between 2009-2020 about zakat indexed in Scopus in Q1, Q2, and Q3. Using a qualitative and quantitative approach, the Bibliometric method and Systematic Literature Review (SLR). This study uses Vos Viewers software and Publish or Perish.Findings – It is known that three sub-themes dominate the research related to zakat: Implementation of zakat in alleviating poverty, zakat compliance, and distribution of zakat funds.Implications – This study implied that regulators can re-evaluate their regulations regarding zakat collection, management, and distribution. This is because they expect researchers, practitioners, and regulators to establish and implement policies for the future.Originality – It identifies three sub-themes that dominate research related to zakat, they are Implementation of zakat in alleviating poverty, compliance with zakat, and distribution of zakat funds.